Cancer diagnosis and mortality in patients with ankylosing spondylitis: A Western Australian retrospective cohort study. (30th November 2020) - Kelty, Erin; Raymond, Warren; Inderjeeth, Charles; Keen, Helen; Nossent, Johannes; Preen, David B.
Abstract: Aim: Ankylosing spondylitis (AS) has been associated with a modest increase in the risk of cancer. However, little is known as to how AS influences risk of mortality following cancer diagnosis. This study compared the risk of cancer and subsequent mortality in patients with AS compared with a non‐AS population group. Methods: Patients diagnosed with AS in Western Australia (WA) between 1980 and 2014 were identified from the WA Rheumatic Disease Epidemiological Register (N = 2152; 31 099 patient‐years). A non‐AS comparison group (N = 10 760; 165 609 patient‐years) was selected from hospital records, matched 1:5 on age, Aboriginality, and gender. Data on cancer diagnosis, comorbidities and mortality were extracted from state cancer, hospital, and mortality registers. The relative risk of cancer (overall and by type) and mortality following cancer diagnosis between AS and non‐AS comparators was compared using Cox proportional hazard models, adjusting for risk factors and comorbidities. Results: Ankylosing spondylitis patients had a 15% increase in the crude risk of cancer (hazard ratio [HR]: 1.15, 95% CI: 1.02‐1.30). However, this association was attenuated following adjustment for smoking and common comorbidities (adjusted HR: 1.08, 95% CI: 0.95‐1.22). Following a cancer diagnosis, patients with AS had an increased risk of 5‐year mortality in the unadjusted (HR: 1.24, 95% CI: 1.03‐1.49) and the adjusted models (adjusted HR: 1.37, 95% CI: 1.13‐1.66). Conclusion: Ankylosing spondylitis was not associated with an increased risk of cancer diagnosis. Following a cancer diagnosis, AS was associated with an increased risk of 5‐year mortality.